1984
DOI: 10.1177/036354658401200508
|View full text |Cite
|
Sign up to set email alerts
|

Patellar and quadriceps tendon ru p tures— jumper's knee

Abstract: We reviewed 13 patients with end stage jumper's knee, 10 with patellar tendon ruptures, and 3 with ruptures of the quadriceps tendon to evaluate our long-term results in treating these tendon ruptures in an athletic population. The focus was on the natural history, the time until return, and the level of return, to athletic activity. Jumper's knee affected all patients to a varying degree prior to rupture. Basketball was the most common sport involved. At followup, averaging 4 1/2 years, patients underwent fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(123 citation statements)
references
References 7 publications
6
109
1
4
Order By: Relevance
“…Then some authors 8, 9 [6] [7] suggest that when they occur after 40 years The taking of fluoroquinolones or a repeated corticoid infiltration, or anabolisant steroid abuse are also reported as promoting factors [9]. Those pathologies are sources of reshuffle (amyloid deposit, collagen synthesis alteration, tendons vascularisation alteration) linked to a chronic inflammation which weakens tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Then some authors 8, 9 [6] [7] suggest that when they occur after 40 years The taking of fluoroquinolones or a repeated corticoid infiltration, or anabolisant steroid abuse are also reported as promoting factors [9]. Those pathologies are sources of reshuffle (amyloid deposit, collagen synthesis alteration, tendons vascularisation alteration) linked to a chronic inflammation which weakens tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiographs were not usually informative. Kelly et al (1984) repaired the partial quadriceps tendon ruptures with nonabsorbable sutures passed through patellar drill holes. Although the number of cases was small in their study, their results of surgical treatment of partial rupture of the quadriceps tendon were inferior to those of the patellar tendon.…”
Section: Discussionmentioning
confidence: 99%
“…It is most commonly seen at the inferior pole of the patella at the origin of the patellar tendon, hut i n about one fourth of the cases it may be locnted at the insertion of the quadriceps tendon (Perugia et al 1977). Conservative treatment is usually successful, but some cases progress to a chronic stage, with a partial or even complete rupture of the tendon, and operative treatment is required (Kelly et al 1984). We report here the results of 28 cases, in which jumper's knee in the quadriceps tendon was treated surgically.…”
Section: ~~ ~mentioning
confidence: 99%
“…Kelly et al (9) also reported a variety of disrup tions: midsubstance, distal pole avulsion, tibial tubercle avulsion, and combined inferior/superior avulsion. T w o ruptures were in the patellar midsubstance; one avulsed medially from the distal pole of the patella and laterally from the tibial tubercle, and one case was an inverted U , where the medial and lateral portions of the tendon ruptured from the tibia1 tubercle and the midportion from the distal pole of the patella (9).…”
Section: Abstract: Patellar Tendon Rehabilitation Electrical Stimumentioning
confidence: 99%